Desmoid tumors of the abdominal wall: A case report - Overhaus, Marcus (BioMed Central, 2003)
BACKGROUND: Desmoid tumors are slow growing deep fibromatoses with aggressive infiltration of adjacent tissue but without any metastatic potential. CASE PRESENTATION: We report on two female patients with desmoid tumor of the abdominal wall who underwent primary resection. Both patients had a history of an earlier abdominal surgery. Preoperative evaluation included abdominal ultrasound, magnetic resonance imaging and computed tomography. The histology in both cases revealed a desmoid tumor. CONCLUSION: Complete surgical resection is the first line management of this tumor entity.